Determinasi Harga Saham Perusahaan Terkategori SRI-KEHATI yang Terdaftar di BEI Periode 2017-2021 - Yuliansyah, Fadilah; Nurhayati, Nurhayati (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2024)
This study aims to analyze and prove the effect of Price Earnings Ratio, Return On Equity, Earnings Per Share, Price to Book Value, and Return On Asset on stock prices of companies categorized as SRI-KEHATI listed on the Indonesia Stock Exchange for the period 2017-2021. Samples are obtained using the purposive sampling technique, and we got a selection of 25 companies. Data analysis in this study used multiple linear regression analysis. The results showed that simultaneously Price to Book Value, Earnings Per Share, Return on Asset, Price Earnings Ratio, and Return on Equity significantly affected stock prices. Partially Return on Asset and Price to Book Value has no significant impact on stock prices.